Review of Graft-Versus-Host Disease - Ramachandran, Vignesh; Kolli, Sree S.; Strowd, Lindsay C. (Dermatologic clinics, 2019)
Graft-versus-host disease (GVHD) is an adverse immunologic phenomenon following allogenic hematopoietic stem cell transplant. Cutaneous manifestations are the earliest and most common presentation of the disease. This article describes the pathophysiology, clinical presentation, diagnosis, and treatment options available for acute and chronic GVHD. Acute and chronic GVHD result from an initial insult triggering an exaggerated inflammatory cascade. Clinical presentation for cutaneous acute GVHD is limited to maculopapular rash and oral mucosal lesions, whereas chronic GVHD can also include nail, scalp, and genitalia changes. Diagnosis is often made clinically and supported by biopsy, laboratory and radiology findings.